Orthodontic movement in deciduous teeth - Alberto Consolaro (Dental Press Editora, 2015)
Deciduous teeth exfoliate as a result of apoptosis induced by cementoblasts, a process that reveals the mineralized portion of the root while attracting clasts. Root resorption in deciduous teeth is slow due to lack of mediators necessary to speed it up; however, it accelerates and spreads in one single direction whenever a permanent tooth pericoronal follicle, rich in epithelial growth factor (EGF), or other bone resorption mediators come near. The latter are responsible for bone resorption during eruption, and deciduous teeth root resorption and exfoliation. Should deciduous teeth be subjected to orthodontic movement or anchorage, mediators local levels will increase. Thus, one should be fully aware that root resorption in deciduous teeth will speed up and exfoliation will early occur. Treatment planning involving deciduous teeth orthodontic movement and/or anchorage should consider: Are clinical benefits relevant enough as to be worth the risk of undergoing early inconvenient root resorption?